Cidades sustentáveis e parques: reflexões teórico-conceituais - Marcos Antônio Silvestre Gomes (Confins)
This article intends to reflect on urban parks and sustainability, by evidencing projects when both were either not in alignment and recurrent analysis of literature under the guidelines from the United Nations' imposed global agenda. The work results from bibliographical research, project observations, field visits and specific analyzes of parks, at national and international level, especially in Rio de Janeiro (Brazil) and Lisbon (Portugal). It has demonstrated that, even after two decades of the signing of Agenda 21, the term sustainable development is widelyused by public and private agents who, with different meanings and intentions, set their discourses and actions to the ideals of urban sustainability, claiming the parks as one of the elements of these practices. It is also demonstrated that studies on cities, parks andsustainability still lack of theoretical and conceptual advances that allow for the demystification of discourses and practices in the production of urban space.